Empowering Chinese university health service providers to become mental health champions: insights from the ACE-LYNX intervention - Wang, Fenghua; Gao, Jianguo; Hao, Suyu; Tsang, Ka Tat; Wong, Josephine Pui-Hing; Fung, Kenneth; Li, Alan Tai-Wai; Jia, Cunxian; Cheng, Shengli (Frontiers in Psychiatry, 2024)
Background: Evidence shows that there is a high prevalence of mental health challenges including depression and anxiety, among Chinese university students. Providing mental health care providers with professional training is crucial to implementing effective mental health promotion initiatives in university settings. Globally, the focus of the mental health system is shifting to recovery and the importance of empowerment is increasingly being emphasized. There is a call to integrate empowerment education into professional training programs for health service providers with the goal of mobilizing them to become mental health champions capable of advancing mental health care.The ACE-LYNX (Acceptance and Commitment to Empowerment-Linking Youth and Xin i.e., "heart(s)" in Chinese) intervention took place at six universities in Jinan, Shandong Province, China. It aimed to promote mental health literacy and build capacity among mental health service providers (MHSPs) to enable them to become mental health champions at their universities and beyond. A total of 139 university MHSPs participated. In addition, we recruited forty-five participants to take part in three-monthpost-intervention focus group interviews to explore their experiences taking part in ACE-LYNX and applying the knowledge, skills, and insights they gained from the intervention.Result: This paper reports on the effects of empowerment education, which is a key component of ACE-LYNX, on the MHSPs. Four themes were identified: 1) conscious awareness and behavioral change through psychological empowerment users; 2) professional insights and motivation for organizational empowerment; 3) non-self in the continuum of collective empowerment; and 4) interdisciplinary challenges and divergences in empowerment action.We found that it is critical to integrate empowerment education into professional training. The process of MHSPs developing their empowerment practice is characterized by their moving from individual to collective empowerment along a continuum, with organizational and collective empowerment taking place in a longer time frame. Experiential learning, empathy education, and critical reflection accelerated the continuous iterative transformative process of empowerment practices. To advance the integration of empowerment into mental health care, the engagement of organizational decision-makers and policy makers in empowerment training is critical to ensure alignment of empowerment values and competence at all levels of service provision.